Percutaneous CT-Guided Radiofrequency Ablation of Solitary Small Renal Masses: A Single Center Experience - Pieper, C. C.; Fischer, S.; Strunk, H.; Meyer, C.; Thomas, D.; Willinek, W. A.; Hauser, S.; Nadal, J.; Schild, H.; Wilhelm, K. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2015)
Purpose: To analyze the outcome of patients undergoing percutaneous CT-guided radiofrequency ablation (RFA) of small renal masses (SRM) at a single center during a ten-year time period.Materials and Methods: Patient records of renal RFAs (07/2003 – 11/2013) were reviewed. Indications were SRM suspicious of malignancy on imaging and one of the following: severe comorbidity; old age; solitary kidney; impaired renal function; patient wish. Biopsy was performed at the time of RFA. Patients were excluded if no follow-up was available. Patient and procedural characteristics were recorded. Survival rates were calculated using the Kaplan-Meier’s method and compared with log-rank or cox tests.Results: 38 patients (16 females, mean age 70.0 years [range 52 – 87]) presenting with a solitary SRM were included in the study. Biopsy showed malignancy in 29 patients; 9 had benign tumors. 26 patients suffered from cardiovascular, respiratory or hepatic comorbidities. Technical success (complete ablation on first follow-up) was achieved in 95 % of cases. Two major complications (bowel perforation; hematothorax) occurred. The 3- and 7-year overall survival (OS) [any cause] rates were 73.4 ± 0.8 % and 50.3 ± 1.0 %, respectively (mean follow-up 54.6 months, range 1 – 127). 4 recurrences and 2 metastases were observed. The presence of comorbidities was the only independent predictor of OS. There was no difference in survival between patients with benign and malignant tumors.Conclusion: RFA of SRM is successful in a large percentage of cases with a low complication rate and durable local control. As RFA is typically performed in multimorbid patients, overall survival seems to depend primarily on comorbidities rather than cancer progression.Key Points• RFA of SRM is technically successful in the majority of cases.• RFA leads to a high degree of local tumor control.• Post-RFA most patients ultimately die of comorbidities.• Overall survival post-RFA does not significantly differ between benign and malignant tumors in multimorbid patients.Citation Format:• Pieper C. C., Fischer S., Strunk H. et al. Percutaneous CT-Guided Radiofrequency Ablation of Solitary Small Renal Masses: A Single Center Experience. Fortschr Röntgenstr 2015; 187: 577 – 583
Keywords: abdomen; urinary; ablation procedures; radiofrequency (RF) ablation